The Aesthetic Approach To Metaphor In The Formation Of Inner Spaces - Qadir Ahmad Aljaf, Salah Aldiyn (Opción, 2019)
Borrowing began in the designs of the inner spaces long ago, and it was almost related to the existence of man on the face of the earth, and it began to enter into most, if not all, fields of human civilization. And through the production of the first tools used by man, so borrowing has recorded its presence in the industry from its beginnings to this day, which we observe in many companies and institutions concerned in the fields of design and furniture. Different intel- lectual and utilitarian orientations, especially in the production of industrial designs characterized by the character of metaphor by employing some con- cepts and symbols that perform that characteristic, especially environmental, and for the purpose of Fulfilling the requirements of the character of met- aphor in the strict scientific sense. The researcher examined and examined some of these internal spaces and found that there is a kind of deficiency in understanding the cognitive system that bestows on the design forms of meta- phor. One of the issues in which metaphor can perform its aesthetic function in design, which is related to the subject’s aesthetic connotations and stakes, is based on the three foundations that make the recipient choose part of the design work Rather, it places it in front of a test to the other part and the other to reveal ambiguity, as the interpretation factor is required in each technical product as well as the overlapping of meanings and their interaction, which is based on the process of concentration Theoretical mechanisms are correct according to what is stipulated in institutions in which studies have become concerned with borrowing in general, a broad approach to human studies, so that attempts to reveal the causes of multiplicity and its causes, And the diversity in the apparent symbolism of the aesthetic approach must revolve around its emergence from a design language based on metaphor, to form a conclusion produced through the interaction of the designing art- ist with the objective reality, Based on tangible and visual realities. From this introduction, the researcher has a question in formulating a research problem with the following question: What is the format based on the aes- thetic approach to borrowing in the formation of internal spaces?